Volleyball players' guide to safe plyometrics - Brittenham, G. (2012)
Following concepts of training specificity, the physical stress of training should use the predominant energy systems, movement patterns and sport skill fundamentals of competition volleyball. Practice serving to improve serve accuracy. Lift weights to develop strength. Incorporate plyometric training to enhance the speed component of power.